Author's program from combined shaping as a means of improving the physical preparedness of female students - Anastasiia Demchenko (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to improve the level of physical preparedness of female students aged 17-20 by means of combined shaping. Material & Methods: the following research methods were used: analysis and generalization of literary sources, pedagogical experiment, pedagogical testing, methods of mathematical statistics. The experiment involved 30 female students aged 17-20 years of non-special faculties of the Central State Pedagogical University named after Vladimir Vinnichenko. Results: the author's program of sectional sessions on combined shaping for students of 17-20 years is developed. The positive effect of combined shaping on the physical fitness of female students has been revealed. Conclusions: the program of sectional sessions on combined shaping on the dynamics of the basic indicators of the physical readiness of female students.